2011
DOI: 10.1152/ajpcell.00409.2010
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Ca2+ transport and muscle relaxation in skeletal muscle from sarcolipin-null mice

Abstract: To evaluate the physiological significance of SLN in skeletal muscle, we compared muscle contractility and SERCA activity between Sln-null and wild-type mice. SLN protein expression in wild-type mice was abundant in soleus and red gastrocnemius (RG), low in extensor digitorum longus (EDL), and absent from white gastrocnemius (WG). SERCA activity rates were increased in soleus and RG, but not in EDL or WG, from Sln-null muscles, compared with wild type. No differences were seen between wild-type and Sln-null ED… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
77
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 64 publications
(85 citation statements)
references
References 38 publications
7
77
1
Order By: Relevance
“…Oxygen Consumption in Isolated Muscle-Isolated muscle oxygen consumption (17,18) was measured using the TIOX tissue bath system (Harvard Apparatus, Holliston, MA). Soleus muscles from HFD-fed Sln OE and WT mice (n ϭ 3) were isolated, and oxygen consumption was measured during rest and electrical stimulation (20 V, 600-ms pulse every 2 min from 10 -250 Hz).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxygen Consumption in Isolated Muscle-Isolated muscle oxygen consumption (17,18) was measured using the TIOX tissue bath system (Harvard Apparatus, Holliston, MA). Soleus muscles from HFD-fed Sln OE and WT mice (n ϭ 3) were isolated, and oxygen consumption was measured during rest and electrical stimulation (20 V, 600-ms pulse every 2 min from 10 -250 Hz).…”
Section: Methodsmentioning
confidence: 99%
“…After 30 min, caffeine (3 mM, a dose sufficient to cause a sarcoplasmic reticulum Ca 2ϩ leak from RyR1 but not muscle contraction (19)) was added along with electrical stimulation, and isolated muscle oxygen consumption measurements were taken. Baseline oxygen without muscle was subtracted from experimental values to give muscle oxygen consumption (17).…”
Section: Methodsmentioning
confidence: 99%
“…2+ -ATPase (SERCA) activity was assayed using a method modified from Tupling et al (2011;Duhamel et al, 2007 pyruvate kinase and 0.93 mmol l −1 CaCl 2 . This master mix was aliquoted into two Eppendorf tubes, one of which additionally received 1 µl of 40 mmol l −1 cyclopiazonic acid (CPA) to block SERCA activity and provide a measurement of basal ATPase activity.…”
Section: Camentioning
confidence: 99%
“…In contrast, the mechanism of SLN inhibition of SERCA is poorly understood. Previous studies have suggested that SLN can affect the affinity and/or the V max of SERCA pump (22)(23)(24)(25).…”
mentioning
confidence: 99%